Fabrication of BaTiO3, BaSnO3 and Sn-doped BaTiO3 compact layers for enhanced dye sensitized solar cell - R.M. Fiter, Logeswary (2024)
Fossil fuel, non-renewable energy resources used to power up economic necessities need to be replaced with more efficient and renewable resources to reduce greenhouse gases and pollution. Solar energy is a renewable energy that has been studied and developed to explore opportunities to produce efficient and reliable devices to produce electricity. Dye-sensitized solar cells (DSSC) are third-generation solar cells that have an easy fabrication procedure, are low-cost and have good compatibility with flexible substrates. With the aim to replace the commonly used TiO2 as a photoanode in DSSCs, perovskite oxides have attracted considerable attention to be used in DSSCs. Herein, BaTiO3 (BTO), BaSnO3 (BSO) and Sn-doped BaTiO3 (BTSO) were designed and fabricated as a compact layer in DSSC using a spin-coating method. The experiment was designed using response surface methodology with Box-Behnken design (RSM/BBD), consisting of three independent variables to analyze the optimum deposition condition. The interaction between these factors was studied and used to identify the best parameters for DSSC performance. FESEM images of the compact layer showed that an ultrathin layer of the perovskite oxide was fabricated on the ITO substrate. FTIR spectra revealed that the distinctive peaks for each compact layer were present. The presence of the thin perovskite oxide on the ITO substrate was further validated using XPS measurement. The addition of those compact layers successfully reduced the leakage current, proofing that the perovskite oxides can be used as a good blocking material to suppress the back electron movement from the transparent conductive oxide to the electrolyte. DSSC with compact layers revealed a higher back charge transfer resistance between metal oxide/dye and electrolyte and longer electron lifetime (τe) compared to DSSC without compact layers, illustrating that the recombination effect was decreased and the compact layer aids in the separation of photogenerated charge carriers to increase the photovoltaic performance of the solar cell. The optimized conditions for the compact layers were as follows: BaTiO3 (annealing duration: 3 hours, annealing temperature: 485°C and number of dropcasting: 3 times), BaSnO3 (annealing duration: 2 hours, annealing temperature: 540°C and number of dropcasting: 2 times) and Sn-doped BaTiO3 (annealing temperature: 460°C, percentage of Sn precursor: 41% and number of dropcasting: 3 times). All the perovskite oxide-based compact layers illustrated a good fit towards the quadratic model in the Box-Behnken design with an appreciable coefficient of determination (R2). All three compact layers attained enhanced photocurrent of 12.02 mA cm-2, 12.40 mA cm-2 and 14.70 mA cm-2 compared to DSSC without a compact layer with photocurrent of 9.60 mA cm-2. The improvement in the photocurrent was attained due to the increase in the concentration of photogenerated charge carriers, improving the efficiency of the DSSC. DSSC containing the BTO, BSO and BTSO compact layers exhibited enhancement of power conversion efficiency (PCE) of 4.95%, 4.82% and 5.33%, respectively compared to DSSC without a compact layer (3.54%). Thus, BTO, BSO and BTSO compact layers can be used to accelerate the generation and transportation of charge carriers and suppress the recombination.